LEGAL PROTECTION FOR CONSUMERS DUE TO EXPIRED FOOD PRODUCTS BASED ON LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Moggy Maulana; Teuku Saiful Bahri (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
This research is aimed at answering questions about the government's role in protecting consumers. to food products, and the responsibility of producers to consumers in handling consumer complaints related to food products that are not suitable. This is a qualitative research with a normative legal research approach, namely library law research. The procedure in this study was carried out by selecting themes, exploring information, determining research directions, collecting data sources, presenting data, and compiling research reports. Meanwhile, this study used qualitative data analysis techniques based on literature data about research variables. The results of this study indicate that the government's role in protecting consumers against food and beverage products that have expired is to develop consumer protection in Indonesia and to implement law enforcement on applicable laws and regulations.A form of consumer protection provided by the government as a protector of the consumer community and also as a coach for business actors. While the handling of consumer complaints related to the circulation of expired food products is carried out by the Food and Drug Monitoring Agency (BPOM) by opening a service unit that accommodates all consumer complaints.